Antioxidant activity comparison of Purnajiwa fruit (Kopsia arborea Blume.) extracted using different solvents and methods - Sasadara, Maria Malida Vernandes (International Journal of Biosciences and Biotechnology; Vol 12 No 1 (2024): International Journal of Biosciences and BiotechnologyDO - 10.24843/IJBB.2024.v12.i01.p02, 2025)
The choice of extraction method can significantly influence the phytochemical profile and antioxidant activity of the obtained extracts. Purnajiwa ( Kopsia arborea Blume.) is a potential medicinal plant that can be developed into traditional medicine. Purnajiwa has been the subject of several studies focusing on its phytochemical composition and antioxidant activity. This study was experimental research to compare the antioxidant activity (IC50) of purnajiwa extracted using two different methods (maceration and soxhlet) and solvents (ethanol and methanol). Data were analyzed statistically using one-way and two-way ANOVA to compare and evaluate the differences in the data with a 95% confidence level. Research showed that methanol and soxhlet produced extract with lower IC50 than ethanol. Additionally, using methanol solvent with the soxhlet method produced the lowest IC50, indicating the highest antioxidant activity compared to other groups. In conclusion, using methanol and soxhlet is the optimal method and solvent in purnajiwa extraction.